Dual Mechanisms of Metabolite Acquisition by the Obligate Intracytosolic Pathogen Rickettsia prowazekii Reveal Novel Aspects of Triose Phosphate Transport - Frohlich, Kyla M. (American Society for Microbiology, 2013)
Rickettsia prowazekii is an obligate intracytosolic pathogen and the causative agent of epidemic typhus fever in humans. As an evolutionary model of intracellular pathogenesis, rickettsiae are notorious for their use of transport systems that parasitize eukaryotic host cell biochemical pathways. Rickettsial transport systems for substrates found only in eukaryotic cell cytoplasm are uncommon among free-living microorganisms and often possess distinctive mechanisms. We previously reported that R. prowazekii acquires triose phosphates for phospholipid biosynthesis via the coordinated activities of a novel dihydroxyacetone phosphate transport system and an sn-glycerol-3-phosphate dehydrogenase (K. M. Frohlich et al., J. Bacteriol. 192:4281–4288, 2010). In the present study, we have determined that R. prowazekii utilizes a second, independent triose phosphate acquisition pathway whereby sn-glycerol-3-phosphate is directly transported and incorporated into phospholipids. Herein we describe the sn-glycerol-3-phosphate and dihydroxyacetone phosphate transport systems in isolated R. prowazekii with respect to kinetics, energy coupling, transport mechanisms, and substrate specificity. These data suggest the existence of multiple rickettsial triose phosphate transport systems. Furthermore, the R. prowazekii dihydroxyacetone phosphate transport systems displayed unexpected mechanistic properties compared to well-characterized triose phosphate transport systems from plant plastids. Questions regarding possible roles for dual-substrate acquisition pathways as metabolic virulence factors in the context of a pathogen undergoing reductive evolution are discussed.